STUDI PERENCANAAN TUBUH BENDUNGAN GONGSENG DI KECAMATAN TEMAYANG KABUPATEN BOJONEGORO PROVINSI JAWA TIMUR - Syahril Arifudin; Eko Noerhayati; Bambang Suprapto (Universitas Islam Malang, 2020)
Given the river in Bojonegoro Regency has the difference in average water discharge in the dry season and in the rainy season is relatively large, the construction of the Gongseng Dam prioritized to meet the demands of the society more tangible and urgent, namely to develop agriculture and increase the supply of irrigation water, as well as the provision of raw water to the region of Bojonegoro regency. From the study obtained dimensions of dam body design based on the Q1000th and controlled by the QPMF among others the height of 3m, peak elevation + 94.00 m, the peak width of the dam 8 m, slope upstream 1:2.60 m and a downstream slope 1:2.50 m. Further stability analysis is reviewed under normal and earthquake, the stability of the upstream slope on the reservoir empty 1.5 3.21 normal state of , the stability of the upstream slope on an empty reservoir of SF earthquake = 1.48 > 1.2 (safe), the stability of the upstream slope on NWL Reservoir of normal state of SF = 2.40 > 1.5 (safe), upper slope stability of NWL reservoir of SF earthquake = 1.63 > 1.2 (safe), upstream slope stability on FWL reservoir of normal state of SF = 2.31 > 1.5 (safe), upstream slope stability in FWL reservoir of SF earthquake = 1.27 > 1.2 (safe), the stability of downstream slope on the reservoir is empty normal state of SF = 1.62 > 1.5 (safe).Keywords: Dreging Dam Stone, dam dimensions, dam stability